2012
DOI: 10.5812/numonthly.5251
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Nephrolitiasis in Adult Individuals

Abstract: BackgroundNephrolithiasis is a widespread multifactorial disorder. Constitutional, environmental and genetic factors play a role in stone formation. Although important advances have been made in understanding the pathophysiology of stone formation, none of the many theories have given a satisfactory explanation of this process.ObjectivesThe objective of study was to evaluate the probable relationship between cigarette smoking and nephrolitiasis in adult men.Patients and MethodsA total of 102 cases diagnosed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 24 publications
4
27
1
3
Order By: Relevance
“…This study also found that smoking habits among men increased the risk of KSD by 16%, as reported by a casecontrol study on 102 cases diagnosed with nephrolithiasis and 121 age-matched healthy controls in the Iranian population (Tamadon et al 2013). Tobacco consumption will increase serum levels of cadmium and thus increase the risk of KSD (Scott et al 1982).…”
Section: Multivariate Analysissupporting
confidence: 55%
See 1 more Smart Citation
“…This study also found that smoking habits among men increased the risk of KSD by 16%, as reported by a casecontrol study on 102 cases diagnosed with nephrolithiasis and 121 age-matched healthy controls in the Iranian population (Tamadon et al 2013). Tobacco consumption will increase serum levels of cadmium and thus increase the risk of KSD (Scott et al 1982).…”
Section: Multivariate Analysissupporting
confidence: 55%
“…In terms of lifestyle factors, physical activity has been shown to reduce the risk of KSD by 31% (Sorenson et al 2014). Smoking habits have also been shown to increase the risk of KSD (Tamadon et al 2013). Numerous dietary factors such as protein, fibre, calcium, oxalate and specific beverages, as reported in previous studies, can alter urinary composition and super-saturation, but the findings were not consistent (Siener 2006).…”
Section: Introductioncontrasting
confidence: 49%
“…38 Our findings suggest that similar mechanisms may also be activated in response to PM. Similarities between PM and smoking may also suggest a potential role of renal calcium handling, 39,40 but unfortunately, no data about renal calcium was available in the BACH/Bone cohort.…”
Section: Discussionmentioning
confidence: 99%
“…10 In addition, the influence of smoking on urolithiasis has only been scarcely examined. [11][12][13] Furthermore, there is no consistent evidence about the effects of physical inactivity and smoking on urolithiasis. Therefore, the aim of the present study was to evaluate relationships between leisure time physical activity (LTPA) and other modifiable risk …”
Section: Introductionmentioning
confidence: 99%